ความคาดหวังและความพึงพอใจของนักท่องเที่ยวชาวไทยต่อการจัดการ สภาพแวดล้อมบริเวณชายหาดแม่รําพึง จังหวัดระยอง - เสริมศรี สุพรรณี; แก้วนุช กนกกานต์ (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2015)
วัตถุประสงค์ของการศึกษานี้มี 3 ประการได้แก่ 1) เพื่อศึกษาความคาดหวังและความพึงพอใจ 2) เพื่อศึกษาความสัมพันธ์ระหว่างความคาดหวังและความพึงพอใจ และ 3) เพื่อศึกษาความสัมพันธ์ ระหว่างปัจจัยส่วนบุคคลและปัจจัยสนับสนุนที่มีต่อความคาดหวังและความพึงพอใจของนักท่องเที่ยว ชาวไทยต่อการจัดการสภาพแวดล้อมบริเวณชายหาดแม่รําพึง จังหวัดระยอง กลุ่มตัวอย่างที่ใช้ใน การศึกษาครั้งนี้ คือ นักท่องเที่ยวชาวไทยที่มาเที่ยวบริเวณชายหาดแม่รําพึง จังหวัดระยอง จํานวน 100 คน ใช้แบบสอบถามเป็นเครื่องมือ แล้วนําไปวิเคราะห์ด้วยโปรแกรมสําเร็จรูป ผลการศึกษาพบว่ากลุ่ม ตัวอย่างส่วนใหญ่มีความคาดหวังต่อการจัดการสภาพแวดล้อมบริเวณชายหาดแม่รําพึง จังหวัดระยอง ในระดับที่มาก แต่กลับมีความพึงพอใจเพียงปานกลาง ผลการศึกษาความสัมพันธ์ระหว่างความคาดหวัง และความพึงพอใจต่อการจัดการสภาพแวดล้อมบริเวณชายหาดแม่รําพึง ไม่มีความสัมพันธ์กันในทุกๆ ด้าน ผลการศึกษาด้านปัจจัยส่วนบุคคล ซึ่งได้แก่ อายุ อาชีพ รายได้ ที่แตกต่างกันมีความคาดหวังต่อ การจัดการสภาพแวดล้อมบริเวณชายหาดแม่รําพึงที่แตกต่างกันอย่างมีนัยสําคัญทางสถิติ ปัจจัยส่วน บุคคลของนักท่องเที่ยวในด้านรายได้ที่แตกต่างกัน มีความพึงพอใจต่อการจัดการสภาพแวดล้อมบริเวณ ชายหาดแม่รําพึงแตกต่างกันอย่างมีนัยสําคัญทางสถิติ The study has 3 objectives as follow: 1) to study the expectation and satisfaction, 2) to study the relationship between their expectation and satisfaction and 3) to study the relationship between personal factors and supporting factors towards the expectation and satisfaction of Thai tourists towards the environmental management in the area of Mae Ram Phung beach, Rayong Province. The sample of this study was 100 Thai tourists who visited Mae Ram Phung beach in Rayong Province. A questionnaire was used as a tool for the collection of data. Then, the data were analyzed by computer programs. The results of the study can be concluded as follow: the majority of tourists in the sample group had high expectation. On the other hand, the level of their satisfaction towards the environmental management in the area of Mae Ram Phung beach was medium. According to the result of the study of the relationship between the tourists’ expectation and satisfaction, it was found out that the sample group’s expectation and satisfaction were not related in all 3 aspects. The result of the study of personal factors of the tourists in terms of age, occupation and income showed that these factors caused different expectation towards the environmental management in the area of Mae Ram Phung beach with statistical significance. The result of the study of personal factors of the tourists in terms of income showed that this factor caused different satisfaction towards the environmental management in the area of Mae Ram Phung beach with statistical significance.